Homeless in the homeland: Housing protests in Kazakhstan. (June 2018) - Alexander, Catherine
This article tracks housing protests in Kazakhstan's former capital city, Almaty, from 1989 to 2016 for what they reveal about shifting ideas of rights and obligations between citizens and state. Three broad models of moral economies of housing emerge: the first, during the Soviet period, where equal access to housing was nominally in return for labour; the second, during the early Republican period when pro-Kazakh policies favoured previously marginalised ethnic Kazakhs, and, the third, in the period 2004 – 2008, when the country's wealth increased, before the financial crash and the plunging value of the local currency. This last period was when a professional class was increasingly valorised by the government with housing support mechanisms created specifically for them. Protests in each period highlight the failures of each model to provide secure, adequate housing. A constant theme of 'illegal legality' and informal practices, variously construed by citizens as moral, pragmatic or immoral, have consistently undermined both the achievement of housing promises and the safety and security of housing. The article explores the paradox of why citizens continue to demand help and interventions from the state amidst such pervasive untrustworthiness.